Roles of Carotenoids in Invertebrate Immunology - Tan, Karsoon; Zhang, Hongkuan; Lim, Leong-Seng; Ma, Hongyu; Li, Shengkang; Zheng, Huaiping (Frontiers in Immunology, 2020)
Carotenoids are biologically active pigments that are well known to enhance the defense and immunity of the vertebrate system. However in invertebrates, the role of carotenoids in immunity is not clear. Therefore, this study aims to review the scientific evidence for the role of carotenoids in invertebrate immunization. From the analysis of published literatures and recent studies from our laboratory, it is obvious that carotenoids are involved in invertebrate immunity in two ways. On the one hand, carotenoids can act as antioxidant enzymes to remove singlet oxygen, superoxide anion radicals and hydroxyl radicals, thereby reducing SOD activity and reducing the cost of immunity. In some organisms, carotenoids have been shown to promote SOD activity by up-regulating the expression of the ZnCuSOD gene. Carotenoids, on the other hand, play a role in the expression and regulation of many genes involved in invertebrate immunity, including Thioredoxins (TRX), Peptidoglycan recognition receptor proteins (PGRPs), Ferritins, Prophenoloxidase (ProPO), Vitellogenin (Vg), Toll-like Receptor (TLRs), Heat shock proteins (HSPs) and CuZnSOD gene. The information in this review is very useful for updating our understanding of the progress of carotenoid research in invertebrate immunology and to help identify topics for future topics.